MicroRNA‐30a ameliorates hepatic fibrosis by inhibiting Beclin1‐mediated autophagy. Issue 12 (1st August 2017) - Chen, Jianliang; Yu, Yue; Li, Shu; Liu, Yuting; Zhou, Shu; Cao, Shouji; Yin, Jie; Li, Guoqiang
Abstract: We explored the role of microRNA‐30a (miR‐30a) and the mechanism involved in hepatic fibrosis. MiR‐30a overexpression was achieved by miR‐30a mimics transfection in hepatic stellate cells (HSCs) (HSC‐T6, LX‐2), and miR‐30a agomir (ago‐miR‐30a) treatment in mice. MiR‐30a levels were measured using TaqMan miRNA assay system, and the localization of miR‐30a was detected by fluorescence in situ hybridization (FISH). The interaction of miR‐30a and Beclin1 was confirmed by dual‐luciferase reporter assay. Autophagic flux was analysed using tandem mRFP‐GFP‐LC3 fluorescence microscopy, electron microscopy and Western blot of LC3‐II/I ratio. MiR‐30a was notably down‐regulated in activated HSCs and LX‐2‐exosomes induced by TGF‐β1; overexpression of miR‐30a down‐regulated extracellular matrix (ECM), such as α‐SMA, TIMP‐1, and Collagen I expression, and suppressed cell viability in HSCs. MiR‐30a was significantly down‐regulated in hepatic fibrosis mice and overexpression of miR‐30a prevented BDL‐induced fibrogenesis, concomitant with the down‐regulation of ECM. MiR‐30a inhibited HSCs autophagy and increased lipid accumulation in HSCs and in mice fibrotic hepatic tissues. MiR‐30a inhibited its downstream effector of Beclin1 by direct targeting its 3′‐UTR region. Moreover, Knock‐down of Beclin1 by small interfering RNA (siRNA) inhibited HSC autophagy and activation in LX‐2 cells. In conclusion, miR‐30a is down‐regulated in hepatic fibrosis models and its overexpression prevents liver fibrogenesis by directly suppressing Beclin1‐mediated autophagy; therefore, miR‐30a may be a new potential therapeutic target for controlling hepatic fibrosis.